Läkemedel som förebygger och behandlar trombos hos hund och katt - Leijonmarck, Caroline (2011)
Several diseases increase the risk of thrombosis in dogs and cats, often with a fatal outcome. Currently there are no definite treatment guidelines for the use of thrombolytic and thromboprofylactic agents in veterinary medicine. None of these drugs are approved for dogs and cats in Sweden. Medicines aimed for humans have been used tentatively. This literature study is an investigation of what is currently known about the effects and safety of these pharmacological agents when used for dogs and cats. Streptokinase and recombinant tissue plasminogen activator (rtPA) are used when clots need to be dissolved emergently. They have significant thrombolytic effects in dogs however in cats the results are varied and multiple adverse effects have been seen. Among the drugs used to prevent thrombosis adverse effects were minimal for low molecular weight heparins, acetylsalicylic acid and clopidogrel. Warfarin on the other hand was associated with severe adverse effects in cats. In vitro testing of blood samples from treated animals indicated that prophylactic effects could be achieved by all of the drugs. However, there was an individual variety in the response to acetylsalicylic acid and clopidogrel in dogs and to warfarin in cats. There are also few studies to confirm a decreased prevalence of thrombosis in predisposed animals and in general the numbers of animals included in the studies are small. At this point it is doubtful if treatment of dogs and cats with these drugs can be motivated.